1985
DOI: 10.2224/sbp.1985.13.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Issues in Research on Field Dependence-Independence

Abstract: This paper attempts to evaluate some conceptual and methodological issues in research on field dependence-independence. Problems of the definition and measurement of "psychological differentiation" and "cognitive restructuring" are examined. Difficulties arising from the profusion of measures, inadequate control of intelligence and insufficient construct validation of tests are also considered. The paper concludes with some recommendations for further research in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Considering the distinction between FDI and general intelligence the question of what specific abilities FDI represents is crucial to fully understanding the construct, as emphasized by Moran (1985). Relative to this need for specification, Sternberg (1997) concluded, ''field independence is tantamount to spatial ability'' based on the work of MacLeod et al (1986) who analyzed two widely used measures of spatial ability with scores of FDI.…”
Section: Visuospatial and Executive Functioning In Working Memorymentioning
confidence: 99%
“…Considering the distinction between FDI and general intelligence the question of what specific abilities FDI represents is crucial to fully understanding the construct, as emphasized by Moran (1985). Relative to this need for specification, Sternberg (1997) concluded, ''field independence is tantamount to spatial ability'' based on the work of MacLeod et al (1986) who analyzed two widely used measures of spatial ability with scores of FDI.…”
Section: Visuospatial and Executive Functioning In Working Memorymentioning
confidence: 99%
“…The disagreement among different studies might be accounted for by the use of different tests in the measurement of cognitive styles that, according to different authors (Moran, 1985;MacGavary, 1979), probably take into account different aspects of field dependence-independence and are related to different personal characteristics, especially for the different dimensions of intelligence. However, Raviv and Nabel (1990) have shown that, when scores on both the Embedded Figures Test and the Oltman portable rod-and-frame test are compared for adolescents, similar scores are obtained for both measures, with nonathletes being relatively more field-independent than athletes involved in various sports.…”
Section: Source Of Variationmentioning
confidence: 99%
“…The most representative and frequently applied theory from the wholistic-analytic cognitive style family is the field independence-dependence cognitive style (FDI), based on Witkin's theory of psychological differentiation (Witkin et al, 1977) and cognitive restructuring (Witkin & Goodenough, 1981). However, similarly to other theories of cognitive style, FDI has often received criticism (for a review, see Messick, 1984;Tiedemann, 1989;Moran, 1985;Álvarez-Montero et al, 2018;Coffield et al, 2004;Curry et al, 1990;Cassidy, 2004;Kozhevnikov, 2007). Besides problems stemming from vague conceptualization, other theoretical shortcomings and a resulting range of frequently unrelated and unconnected dimensions (Kozhevnikov et al, 2014;Riding & Cheema, 1991;Sternberg & Grigorenko, 1997), the theory's main shortcoming is in insufficient evidence for its convergent validity.…”
Section: Old Controversymentioning
confidence: 99%